Gastrointestinal Bleeding in Cirrhotic Patients with Portal Hypertension. (22nd July 2013) - Biecker, Erwin
Abstract : Gastrointestinal bleeding related to portal hypertension is a serious complication in patients with liver cirrhosis. Most patients bleed from esophageal or gastric varices, but bleeding from ectopic varices or portal hypertensive gastropathy is also possible. The management of acute bleeding has changed over the last years. Patients are managed with a combination of endoscopic and pharmacologic treatment. The endoscopic treatment of choice for esophageal variceal bleeding is variceal band ligation. Bleeding from gastric varices is treated by injection with cyanoacrylate. Treatment with vasoactive drugs as well as antibiotic treatment is started before or at the time point of endoscopy. The first-line treatment for primary prophylaxis of esophageal variceal bleeding is nonselective beta blockers. Pharmacologic therapy is recommended for most patients; band ligation is an alternative in patients with contraindications for or intolerability of beta blockers. Treatment options for secondary prophylaxis include variceal band ligation, beta blockers, a combination of nitrates and beta blockers, and combination of band ligation and pharmacologic treatment. A clear superiority of one treatment over the other has not been shown. Bleeding from portal hypertensive gastropathy or ectopic varices is less common. Treatment options include beta blocker therapy, injection therapy, and interventional radiology.